ATITUDES LINGUÍSTICAS DOS RIKBAKTSA: DISCURSO PÚBLICO SOBRE A LÍNGUA - Oliveira, Mileide Terres de; Rikbaktatsa, Izaudrelia Samasaik (WEB REVISTA SOCIODIALETO, 2018)
Neste trabalho trazemos o povo Rikbaktsa, habitantes de 35 comunidades indígenas situadas no Noroeste do Estado e Mato Grosso. A proposta de nossa pesquisa é de cunho sociolinguístico, em que analisamos as atitudes linguísticas dos Rikbaktsa a partir da situação de contato entre a língua rikbaktsa e o português, em que a atitude linguística consiste no discurso público sobre a língua. Para o referido trabalho, enfatizamos o discurso público sobre a língua a partir de uma pesquisa bibliográfica e coleta de dados realizada por meio de um questionário fechado aplicado a 30 colaboradores bilíngues rikbaktsa/português. Dos resultados encontrados, enfatizamos que a educação indígena é um mecanismo de auxílio para a preservação do idioma nativo, além da formação de professores indígenas capacitados para ministrarem aulas nas aldeias e consequentemente preservar a sua cultura. ABSTRACT: In this work we bring the Rikbaktsa people, inhabitants of 35 indigenous communities located in the Northwest of the State and Mato Grosso. The proposal of our research is sociolinguistic, in which we analyze the linguistic attitudes of the Rikbaktsa from the situation of contact between the language rikbaktsa and the Portuguese, in which the linguistic attitude consists in the public discourse on the language. For this work, we emphasize the public discourse about language from a bibliographical research and data collection carried out through a closed questionnaire applied to 30 bilingual rikbaktsa / Portuguese collaborators. From the results found, we emphasize that indigenous education is an aid mechanism for the preservation of the native language, besides the training of indigenous teachers trained to teach classes in the villages and consequently to preserve their culture. KEYWORDS: Language rikbaktsa; Sociolinguística; Attitudes.